(untitled) (ҚазҰУ Хабаршысы. Биология сериясы, 2015)
UV mutagenesis is a powerful tool for obtaining mutant strains of microalgae for using in biotesting of the polluted aquatic ecosystems. UV irradiation has a strong mutagenic agent, compared with chemical mutagenesis, UV mutagenesis offers many advantages such as less pollution, simple operation, and sterile cultivation condition. In this study the phenotypic characteristics of the wild and mutant strains of the green microalgae Chlamydomonas reinhardtii (CC 1021) were investigated. From the obtained results, selection of the mutant colony after irradiation time 1min. and named CC1021Mut1 strain. The mutant strain showed differences in phenotypic features such as color and size of colonies in the solid medium and also different color in the liquid medium. The mutant cells under microscope appeared different in size and color than the wildtype cells.